2020
DOI: 10.1016/j.compbiomed.2020.103725
|View full text |Cite
|
Sign up to set email alerts
|

Full feature selection for estimating KAP radiation dose in coronary angiographies and percutaneous coronary interventions

Abstract: In interventional cardiology (IC) the radiation dose variation is very significant, and its estimation has been difficult due to the complexity of the treatments. In order to tackle this problem, the aim of this study was to identify the most important demographic and clinical features to estimate Kerma-Area Product (KAP) radiation dose in coronary angiographies (CA) and percutaneous coronary interventions (PCI). The study was retrospective using clinical patient data from 838 CA and PCI procedures. A total of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Our study showed that male patients received significantly higher radiation doses than female patients in abdominal and head CBCT scans. Previous studies have attributed this difference to higher body weight, more complex diseases, and greater technical difficulties that often be seen in male patients [ 19 , 30 ]. However, the CBCT dose analyzed in our study was generated by a single rotation and therefore independent of procedural time or the complexity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that male patients received significantly higher radiation doses than female patients in abdominal and head CBCT scans. Previous studies have attributed this difference to higher body weight, more complex diseases, and greater technical difficulties that often be seen in male patients [ 19 , 30 ]. However, the CBCT dose analyzed in our study was generated by a single rotation and therefore independent of procedural time or the complexity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Elastic net (E-net) is the weighted combination of both L1 and L2 regressions [114]. The linear support vector regressor (lSVR) is another popular regressor for the biomedical prediction problems [115,116]. The features selected by each algorithm are used to train a regression model by the same regression algorithm.…”
Section: E Regression Performance Comparison Of Feature Selection Almentioning
confidence: 99%
“…The greater the credit disbursed compared to public deposits in a bank, the consequence is that the greater the risk that must be borne by the bank concerned. KAP is an assessment of asset quality factors based on the comparison of classified earning assets (APYD) to their earning assets The increase in the KAP ratio is influenced by an increase in APYD or a decrease in total productive costs (Capasso & Neanidis, 2019;Suomi et al, 2020). If the APYD increases, it means that credit is in special attention, substandard credit, doubtful credit, and bad loans also increase.…”
Section: Introductionmentioning
confidence: 99%